2018
DOI: 10.11648/j.ajcem.20180602.14
|View full text |Cite
|
Sign up to set email alerts
|

Canine Rabies Outbreaks, Vaccination Coverage, and Transmission in Humans: Greater Accra Region, Ghana- A Retrospective Study-2006-2011

Abstract: Rabies is a highly fatal, viral, zoonotic disease caused by a Lyssa virus. It is acquired through the bite of an infected animal, mostly dogs. Estimated annual global human mortalities from rabies is 61,000, over 99% of which are from developing countries where about US$583.5 million is spent on its control. Rabies is enzootic in Ghana. Vaccinating about 70% of the dog population leads to a reduction in rabies transmission to humans; however, percentage dog anti-rabies vaccination coverage in Ghana is unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Hence, the percentage rabies vaccination coverage found in this study, was woefully inadequate if rabies is to be controlled. Although there are no specific guidelines for dog vaccination against rabies in Ghana, according to Lopes et al, about 70% of the dog population in the country need to be vaccinated against rabies before a significant reduction in human rabies cases can be achieved [12]. However, the issue of low immunization of dogs against rabies is not peculiar to Ghana and specifically, the Upper East Region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the percentage rabies vaccination coverage found in this study, was woefully inadequate if rabies is to be controlled. Although there are no specific guidelines for dog vaccination against rabies in Ghana, according to Lopes et al, about 70% of the dog population in the country need to be vaccinated against rabies before a significant reduction in human rabies cases can be achieved [12]. However, the issue of low immunization of dogs against rabies is not peculiar to Ghana and specifically, the Upper East Region.…”
Section: Discussionmentioning
confidence: 99%
“…This is because although the Ghana government embarked on a campaign to vaccinate dogs against rabies across the country [11] the campaign was not sustained and has been stopped since 1994 due to lack of sustainable funding and support. Since then, individual dog owners are expected to use their personal income to vaccinate their dogs against rabies either by the government or private veterinary officers [12]. Although there is no documented standardized pricing for anti-rabies vaccination of dogs in Ghana, information from the veterinary division of the Ministry of Agriculture revealed that a shot of anti-rabies vaccine can cost up to $4 per dog.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on rabies in Ghana. These include epidemiology and control measures (Addy, 1985; Alonge & Abu, 1984; Belcher et al., 1976; Lopes et al., 2018); surveillance systems (Afakye et al., 2016; Guri et al., 2020); human rabies outbreaks (Amoako et al., 2021; Apanga et al., 2016; Dsane‐Aidoo et al., 2022; Laryea et al., 2017; Punguyire et al., 2017); dog bites and rabies (Abuh et al., 2017; Addai & Nuertey, 2018; Adomako et al., 2018; Dsane‐Aidoo et al., 2022; Eliezer, 2016; Kenu et al., 2018; Korash & Ameme, 2017; Punguyire et al., 2017, 2020); dog population structure (Tasiame et al., 2019); dog‐associated pig rabies (Tasiame et al., 2016); rabies virus in dogs slaughtered for meat consumption (Tasiame et al., 2021); knowledge, attitudes, perceptions, practices and beliefs (Awuni et al., 2019; Tettey, 1998; Turkson & Wi‐Afedzi, 2020; Vetsi et al., 2021) and lineage of rabies virus in Ghana (Hayman et al., 2011). However, no studies have reported on the space–time pattern of the disease countrywide on a national level.…”
Section: Introductionmentioning
confidence: 99%